(untitled) - Charles Dickens (Hertfordshire Wordsworth Classics, 2000)
David Copperfield is the story of a young man's adventures on his journey from an unhappy & impoverished childhood to the discovery of his vocation as a successful novelist. Among the gloriously vivid cast of characters he encounters are his tyrannical stepfather, Mr Murdstone; his formidable aunt, Betsey Trotwood; the eternally humble yet treacherous Uriah Heep; frivolous, enchanting Dora; & the magnificently impecunious Micawber, one of literature's great comic creations. In David Copperfield-the novel he described as his "favorite child"-Dickens drew revealingly on his own experiences to create one of his most exuberant & enduringly popular works, filled with tragedy & comedy in equal measure. Originally published as a monthly serial, from 4/1849 to 11/1850.
Keywords: Classics; Historical fiction; Fiction